Diagnosis of Two Meningitis Cases Caused by Rickettsia Felis in China, with Metagenomic Next-Generation Sequencing: A Case Report - Wang J; Zhou H; Dong Z; Wang J; Wang R; Guan Y (Infection and Drug Resistance, 2023)
Jie Wang,1,* Hong Zhou,2,* Zan Dong,3 Jing Wang,1 Rui Wang,1 Yuanlin Guan4 1Department of Neurology, First Hospital of Shanxi Medical University, Taiyuan, 030000, People’s Republic of China; 2Graduate School, the First Clinical School of Medicine, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 3Department of Neurology, Yuncheng Central Hospital, Yuncheng, 044000, People’s Republic of China; 4Department of Scientific Affairs, Hugobiotech Co, Ltd, Beijing, 100176, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jie Wang, Department of Neurology, First Hospital of Shanxi Medical University, No. 85 of Jiefang South Road, Taiyuan, Shanxi, 030000, People’s Republic of China, Tel +8613753198116, Email luwanglu2012@163.comBackground: Rickettsia felis is a kind of zoonotic pathogen. Rickettsia felis infections of the central nervous system are rare with only a few cases reported worldwide. The early diagnosis of R. felis is difficult due to its nonspecific clinical features and laboratory tests. Here, we report two meningitis cases caused by R. felis using metagenomic next-generation sequencing (mNGS).Methods: The clinical data of patients with meningitis who were diagnosed to have R. felis through cerebrospinal fluid culture, nuclear magnetic imaging, mNGS detection from January 2019 to December 2019 in The First Clinical Hospital of Shanxi Medical University, were retrospectively analyzed, and their clinical characteristics and disease regression findings were summarized.Case Presentation: The first case was a female patient aged 23 years who was admitted to our hospital presenting with symptoms of headache, fever, and weakness in both lower limbs. Upon examination of spinal imaging, myelitis was diagnosed. However, routine examination and culture of cerebrospinal fluid did not identify the pathogen responsible. Subsequently, metagenomic second-generation sequencing (mNGS) revealed that the infection was caused by R. felis. The patient responded well to standard treatment and showed signs of recovery. The second case was a male patient aged 29 years who was admitted to our hospital with a headache and fever that had persisted for 4 days within a month. Routine examination and culture of the cerebrospinal fluid did not reveal any identifiable pathogens. However, metagenomic second-generation sequencing (mNGS) determined that the patient had a Rickettsial infection likely transmitted by a cat. The patient showed significant improvement after 14 days of doxycycline treatment. Tests for herpes simplex virus, cytomegalovirus, Epstein-Barr virus and tubercle bacillus nucleic acid in the CSF and blood were negative.Therefore mNGS of the cerebrospinal fluid was used, which identified the pathogen as R. felis. One case was diagnosed as subacute meningitis with immune-associated myelitis and the other as subacute meningitis.Conclusion: mNGS of cerebrospinal fluid can be used as a fast and effective method to identify intracranial R. felis infections.Keywords: Rickettsia felis, meningitis, myelitis, metagenomic next-generation sequencing, case report